Grupowe oddziaływania penitencjarne na przykładzie programu dla skazanych młodocianych „Efekt motyla” - Poklek, Robert (Studia Edukacyjne, 2018)
The purpose of serving a prison sentence is not isolating but inducing the perpetrators of crimes to refrain from committing offences in the future. This is possible when there are positive changes in their attitudes, and in particular when they create a need to respect the legal order and a sense of responsibility for their actions. For this purpose, in addition to other means of influence such as work, education, social contacts, cultural and educational activities and sports, or therapy, it is proposed to the detainees to participate in group resocialization programs. The article presents an example of resocialization program dedicated to convicted juveniles entitled “Butterfly Effect”. It presents the theoretical foundations of the program, the spectrum of objectives and results, the methods to achieve them, and scenario activities.